Diamond Open Access publishing in Africa - Kuchma, Iryna; Chiparausha, Blessing; Bruce Lamptey, Richard; Ševkušić, Milica; Smith, Ina (My University, 2024)
Diamond Open Access publishing in Africa - AfricArXiv Open Science Webinar Series 2024 Watch the recording here: https://info-africarxiv.ubuntunet.net/2024/08/15/diamond-open-access-publishing-in-africa/
This webinar session focused on the landscape study of open access publishing in Africa, led by Iryna Kuchma, highlighting the challenges and opportunities of diamond open access journals in Africa. Key points included the need for institutional support, sustainable funding, and the importance of editorial quality and research integrity. Case studies from Zimbabwe, Ghana, and South Africa were presented, emphasizing the need for capacity building, awareness, and advocacy to support diamond open access publishing in Africa.
Keywords: Open Access; Open Science; Diamond Open Access; Publish; Africa; AfricArXiv; Research